TREM-1 and TREM-2 Expression on CD14+ Cells in Bronchoalveolar Lavage Fluid in Pulmonary Sarcoidosis and Hypersensitivity Pneumonitis in the Context of T Cell Immune Response - M. Suchankova; J. Urban; M. Ganovska; E. Tibenska; K. Szaboova; E. Tedlova; F. Sandor; I. Majer; M. Bobovcak; I. Jonner; B. Konig; M. Bucova (Mediators of Inflammation)
Background. Sarcoidosis and hypersensitivity pneumonitis (HP) are immunologically mediated processes caused by hypersensitivity reaction accompanied by similar features including lymphocytic alveolitis and granuloma formation. Recent studies describe the role of TREM receptors in T cell activation, differentiation, and granuloma formation. Alveolar macrophages activation via TREM receptors may be the key factor mediating subsequent immune response. The aim of the study was to analyse TREM-1 and TREM-2 expression to identify further molecular mechanisms participating in the immunopathogenesis of sarcoidosis and HP. Methods. Flow cytometry was performed to analyse TREM-1 and TREM-2 expression on CD14+ cells in bronchoalveolar lavage fluid from patients having sarcoidosis or HP and a control group. Results. The study proved increased TREM-1 expression on alveolar macrophages in pulmonary sarcoidosis and diminished TREM-1 expression in HP-Sarcoidosis: median: 76.7; HP: median: 29.9; control: median: 53.3, (sarcoidosis versus HP: p<0.001; sarcoidosis versus control: p<0.05). TREM-2 expression was increased in both, sarcoidosis and HP-sarcoidosis: median: 34.79; HP: median: 36.00; control: median: 12.98, (sarcoidosis versus control: p<0.05; HP versus control: p<0.05). Correlation analysis showed negative correlation between TREM-1 and total number of CD8+ cytotoxic T cells. In sarcoidosis TREM-1 expression decreased with changes of HRCT image, decrease in CD4/CD8 ratio and decrease in DLCO. Conclusions. Differences in TREM receptor expression in sarcoidosis (increase in TREM-1 and TREM-2) and HP (increase in TREM-2) and correlation analysis suggests that activation via TREM may participate in typical immunological characteristics of sarcoidosis and HP.